A Model for the Development of Philosophy of Sufficiency Economy Learning Center, Ban Nong Waeng School, Bua Ngoen Sub-district, Nam Phong District, Khon Kaen Province - พรมกุล, สุรพล; ภู่สกุล, บุรินทร์; ฮวดศรี, ชาญชัย; ศรเสนา, จีระ; มีโคตรกอง, ประกอบ (Local Administration Journal, 2018)
The objectives of this study were: 1) to develop a model of learning center development according to Philosophy of Sufficiency Economy of Ban Nong Waeng School, Bua Ngoen Sub-district, Nam Phong District, Khon Kaen Province; 2) to try out the developed model; and 3) to evaluate the satisfaction of primary school commissioners, teachers, students, and parents, with the developed model. The sample was a total of 120 persons, i.e., 5 key informants, 10 primary school committees, 5 teachers, 50 students, and 50 parents. The research instruments included questionnaires and interview protocols. Data analysis was done via contextual analysis and basic statistical analysis. The findings are as follows. First, the developed model of learning center development was found to be valid and appropriate. Tactics for student learning improvement were classified into five activity groups: animal husbandry, mushroom cultivation, organic gardening, forest preservation, and gratitude. Second, the mushroom cultivation group had the highest level of performance, followed by the animal husbandry and gratitude groups respectively. Third, parents showed the highest level of satisfaction with the model, followed by the primary school commissioners and students respectively.